A Kinetic Study of CD83 Reveals an Upregulation and Higher Production of sCD83 in Lymphocytes from Pregnant Mice - Packhäuser, Katrin Regina Helene; Roman-Sosa, Gleyder; Ehrhardt, Jens; Krüger, Diana; Zygmunt, Marek; Muzzio, Damián Oscar (Frontiers in Immunology, 2017)
For the normal development of pregnancy, a balance between immune tolerance and defense is crucial. However, the mechanisms mediating such a balance are not fully understood. CD83 is a transmembrane protein which expression has been linked to anti-inflammatory functions of T and B cells. The soluble form of CD83, released by cleavage of the membrane-bound protein, has strong anti-inflammatory properties and was successfully tested in different mouse models. It is assumed that this molecule contributes to the establishment of immune tolerance. Therefore, we postulated that the expression of CD83 is crucial for immune tolerance during pregnancy in mice. Here, we demonstrated that the membrane-bound form of CD83 was upregulated in T and B cells during allogeneic murine pregnancies. An upregulation was also evident in the main splenic B cell subtypes: marginal zone, follicular zone and transitional B cells. We also showed that there was a augmentation in the number of CD83+ cells towards the end of pregnancy within splenic B and CD4+ T cells, while CD83+ dendritic cells was reduced in spleen and inguinal lymph nodes of pregnant mice. Additionally, B lymphocytes in late pregnancy presented a markedly higher sensitivity to LPS in terms of CD83 expression and sCD83 release. Progesterone induced a dosis-dependent upregulation of CD83 on T cells. Our data suggests that the regulation of CD83 expression represents a novel pathway of fetal tolerance and protection against inflammatory threats during pregnancy.